Awareness of Diabetic Complications Among Diabetic Patients Presenting to MMC Mardan (Medical Forum Monthly, 2020)
Objective: To find out whether patients are aware of these complications, which occurs mainly with uncontrolled diabetes and can be a source of significant mortality and morbidity.Study Design: Descriptive/cross-sectional study.Place and Duration of Study: This study was conducted at the Medical B Unit of Mardan Medical Complex (M.M.C), Mardan from September 2019 to December 2019.Materials and Methods: Both male and female diabetic patients were admitted from medical OPD, having minimum duration of diabetes of one year. Patients below 15 years of age were not included in study.Results: Out of 112 patients 44 were male and 68 were female which makes 39.28% and 60.71% respectively. 82 patients were totally illiterate; 26 patients have passed their higher school /inter examination while only 4 patients were graduate. Level of awareness about diabetic complications was poor among females as compared to males, it was also poor among the totally illiterate patients as compared to the ones who have gone through higher school / inter level college or were graduates. Patients with short duration of diabetes were also poorly aware of the complications than those with a long history.Conclusion: Most of the patients with diabetes do not take their disease seriously and are unaware of the complications that can be caused by it. They came to know about complications of the diabetes when they themselves suffer from it and thus causing significant morbidity and mortality. Therefore, it is important that we as physicians not only concentrate on the management of disease but also educate them properly and this should be done both at community and hospital level so as to reduce the morbidity and mortality of the diabetes.